(untitled) (Indian Journal of Animal Production and Management, 2024)
An experiment was conducted to study the biometric parameters of Super Napier green fodder along with assessment of chemical composition, cell wall constituents and fodder characteristics at different days of harvest at Livestock Research Station, Siddarampuram, in Anantapur district. The fodder characteristics of Super Napier i.e., plant height (cm), basal circumference (cm), tillers per plant (number), leaves per tiller (number), leaves per plant (number) increased as age advanced showing a significant difference (P < 0.01) at 15, 30, 45 and 60 days of harvesting. The mean proximate values of Super Napier fodder for DM, CP, CF, EE, TA and NFE were 22.43 ± 2.35, 9.94 ± 1.04, 32.66 ± 1.63, 1.94 ± 0.23, 11.32 ± 1.23 and 44.11 ± 1.47 per cent, respectively. The mean cell wall constituents of NDF, ADF, Hemicellulose, Cellulose, ADL and Silica were 63.64 ± 1.51, 37.90 ± 1.54, 25.74 ±1.47, 27.31 ± 1.74, 8.26 ± 1.31 and 3.38 ± 0.28 per cent, respectively. The leaf area index noticed at the time of harvest was 9.43. The leaf to stem ratio observed at 15th, 30th, 45th and 60th day of harvest was 1.50 ± 0.22, 0.65 ± 0.05, 0.43 ± 0.03 and 0.22 ± 0.11, respectively. Highest leaf to stem ratio was recorded at 15 days of age and lowest at 60 days of age.